Leveraging the Climate-Smart Village (CSV) approach to implement the Integrated Land Management (ILM) concept in FSRP countries - Ganyo, Komla Kyky; Kpadonou, G. Esaïe; Segnon, Alcade Christel; Ouedraogo, Harouna; Tall, Baidy; Lamien, Niéyidouba; Zougmore, Robert Bellarmin (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This deliverable highlights the achievements, perceptions of the participants, lessons learned and outcomes of the regional training workshop on methods and tools for implementing and managing climate-smart villages. The capacity building event was organized in synergy with the FSRP program and targeted national agricultural, meteorological and hydrological services to support the implementation of CSV approach in the FSRP’s intervention areas. As results of the training, five FSRP countries (Burkina Faso, Ghana, Mali, Niger and Sierra Leone) have developed a national plan for implementation of CSV in their respective country with implementation budget ranging from 14,477 to 1,571,086 US $.